2020
DOI: 10.1038/s41467-019-13980-y
|View full text |Cite
|
Sign up to set email alerts
|

Implementing digital computing with DNA-based switching circuits

Abstract: DNA strand displacement reactions (SDRs) provide a set of intelligent toolboxes for developing molecular computation. Whereas SDR-based logic gate circuits have achieved a high level of complexity, the scale-up for practical achievable computational tasks remains a hurdle. Switching circuits that were originally proposed by Shannon in 1938 and nowadays widely used in telecommunication represent an alternative and efficient means to realize fastspeed and high-bandwidth communication. Here we develop SDR-based D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
140
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(149 citation statements)
references
References 36 publications
(50 reference statements)
0
140
0
Order By: Relevance
“…Recently, Fan's group combined TMSD with DNA switching circuits (DSCs) together and realized a set of DSCs-based digital computing functions (such as full-adding), Figure 4E. [43] They demonstrated that arbitrary Boolean functions can be implemented by DSCs with high computing speed, thus providing an inspiring paradigm for biomolecular computing. All above works depend only on the innovation of DNA hybridization technology, the TMSD reaction and fluorophorelabeled DNAs, not on functional materials, which act the leading and enlightening role in DNA computing.…”
Section: Dna Logic Systems Based On Multifarious "Building-block" Matmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Fan's group combined TMSD with DNA switching circuits (DSCs) together and realized a set of DSCs-based digital computing functions (such as full-adding), Figure 4E. [43] They demonstrated that arbitrary Boolean functions can be implemented by DSCs with high computing speed, thus providing an inspiring paradigm for biomolecular computing. All above works depend only on the innovation of DNA hybridization technology, the TMSD reaction and fluorophorelabeled DNAs, not on functional materials, which act the leading and enlightening role in DNA computing.…”
Section: Dna Logic Systems Based On Multifarious "Building-block" Matmentioning
confidence: 99%
“…[42] Copyright 2011, American Chemical Society; E) Switching circuit-based DNA logic system, Reproduced with permission. [43] Copyright 2020, Springer Nature.…”
Section: Aptamersmentioning
confidence: 99%
“…Molecular implementations of this should be possible in the near future for the case of electronic conduction output of photochromic units under various stimulations. 101,102,246 Section 7 mentioned related 212 This fundamental idea is now realized with DNA devices 247 based on toehold-mediated strand exchange. 135 Fig.…”
Section: Msde Reviewmentioning
confidence: 99%
“…The predictable hybridization between complementary base pairs that underlies the self‐assembly of DNA lays the chemical foundation for engineering highly structured materials, dynamic nanodevices and complex reaction networks for molecular computation . Functional DNA nanotechnology has greatly benefited from the extensive use of programmable strand displacement reactions upholding the design of stimuli‐responsive DNA switches, enzyme‐free catalytic systems, or molecular computers .…”
Section: Introductionmentioning
confidence: 99%